Integration of Artificial Intelligence in Physical Education Learning to Improve Learning Quality - Butsiarah Butsiarah (Yayasan Literasi Sains Indonesia, 2025)
This study aims to analyze the impact of integrating Artificial Intelligence (AI) into physical education learning to enhance students’ learning quality. The research employed a quasi-experimental method with a pretest-posttest control group design involving 60 students, divided into experimental and control groups. The research instruments included a learning motivation questionnaire, a student activity observation sheet, and a physical fitness test. The results revealed a significant improvement in the experimental group that applied AI-based learning. The average learning motivation score increased from 72.3 to 88.6 (a 22.5% increase), students’ active participation rose from 68.4% to 90.2%, and physical fitness scores improved from 70.1 to 83.5. The t-test results indicated a significant difference between the experimental and control groups (p < 0.05). These findings demonstrate that the implementation of artificial intelligence technology in physical education can effectively enhance students’ motivation, participation, and learning outcomes. Therefore, integrating AI into the learning process can serve as an innovative and effective strategy to improve the quality of physical education and support the transformation of learning in the rapidly evolving digital era.